Item point identification method based on LKJ operation data - CHEN XINGLAI; DAI DAOWEI; SONG CUNBAO; LI ZHENGQIAN (2020)
The invention discloses an item point recognition method based on LKJ operation data, and the method comprises the following steps: obtaining LKJ operation record data, and extracting the key information of an item point in the data; extracting LKJ data related to the identification item points and recording the LKJ data; analyzing the recorded LKJ data within a period of time to obtain a change trend of the LKJ data, judging whether an item point appears or not according to the change trend, and determining the item point; querying item points corresponding to the current kilometer post in adatabase by adopting a data search algorithm; and comparing the determined item point with the inquired item point so as to correct or insert the record of the item point in the database. The item point in the locomotive running process is updated in real time through the method, so that the safety of railway transportation is ensured. 本发明公开了一种基于LKJ运行数据的项点识别方法，包括以下步骤：获取LKJ运行记录数据、提取该数据中项点的关键信息；提取与识别项点有关的LKJ数据并记录；将记录的一段时间内的